Interešu konflikta novēršana publiskajā iepirkumā. - Lukjanova, Jūlija (Latvijas Universitāte, 2012)
Maģistra darbā „Interešu konflikta novēršana publiskajā iepirkumā” autore aplūko interešu konflikta jēdzienu, kas pēc autores domām Publisko iepirkumu likumā ir sašaurināts un ir jāpaplašina. Visizplatītākie interešu konflikta cēloņi publiskajā iepirkumā ir amatpersonas personīgā tieksme pēc labuma, pārlieku liela amatpersonu rīcības brīvība, publisko iepirkumu procedūras atklātības trūkums, amatpersonu rīcības kontroles trūkums. Tiek aplūkota tāda iepirkumu stadija kā publisko iepirkumu vērtēšana, kas rada vislielākās problēmas interešu konflikta ziņā. Autore uzskata, ka vērtējot pēc kritērija „saimnieciski visizdevīgākais piedāvājums”, jāsalīdzina cenas un pārējo kritēriju attiecība, pie tam cenas attiecībai jābūt lielākai par 40 %, kas garantē visefektīvāko iznākumu. Savukārt kritērija „viszemākā cena’ vērtēšanas gadījumā vislielākās problēmas sagādā piedāvājuma neatbilstība tehniskajai specifikācijai, kas būtu novēršams, uzliekot par pienākumu pasūtītājam pieprasīt papildu informāciju no pretendenta. Autore savā darbā aplūko arī citus interešu konflikta riskus publiskajā iepirkumā, tā piemēram, sekmīgai interešu konflikta novēršanai jāmazina amatpersonu rīcības brīvība, jāpalielina atklātība un jāizveido efektīva amatpersonu rīcības kontrole.

Master's thesis of “Fighting conflict of interests in procurement” deals with the concept of conflict of interest which in the author's view in the Public Procurement Law is very restrictive and should be extended. The most common causes of conflict of interest in procurement are - official has a personal desire for good, too much discretion to the officials, lack of transparency in public procurement procedure, lack of control in officials conduct. Author overviews the procurement phase of the tender evaluation, which account for most problems connected with conflicts of interest. Author believes that in assessing the criterion „the economically most advantageous offer”, criteria „price” rate must be greater than 40%, then it will be the most effective outcome of procurement. While „the lowest price” rating criterion is causing the most problems for the technical specification the author proposes to remedy it by requiring additional information from the applicant. The author deals with other risks of conflicts of interest in public procurement, as for example, the successful prevention of conflict of interest must reduce official discretion, increase transparency and establish effective control of official action.Master's thesis of “Fighting conflict of interests in procurement” deals with the concept of conflict of interest which in the author's view in the Public Procurement Law is very restrictive and should be extended. The most common causes of conflict of interest in procurement are - official has a personal desire for good, too much discretion to the officials, lack of transparency in public procurement procedure, lack of control in officials conduct. Author overviews the procurement phase of the tender evaluation, which account for most problems connected with conflicts of interest. Author believes that in assessing the criterion „the economically most advantageous offer”, criteria „price” rate must be greater than 40%, then it will be the most effective outcome of procurement. While „the lowest price” rating criterion is causing the most problems for the technical specification the author proposes to remedy it by requiring additional information from the applicant. The author deals with other risks of conflicts of interest in public procurement, as for example, the successful prevention of conflict of interest must reduce official discretion, increase transparency and establish effective control of official action.
Preclusion of conflicts of interest in procurement.
Keywords: Juridiskā zinātne